POSSIBILITIES OF APPLICATION OF DIGITAL TECHNOLOGIES IN TOURISM IN THE CONTEXT OF COVID-19 PANDEMY - Khasan Ibragimovich Turdibekov , Sodiq Norkulovich Matlabov , Ibragim Khudoyarovich Nimatov , Yusuf Ibragimovich Turdibekov (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article analyzes the existing opportunities in the development of digital technologies in tourism in the context of the COVID-19 pandemic. In particular, the level of use of Internet communications by potential consumers was studied, and proposals for the introduction of digital communications were developed based on the results of research.